Optimasi Adsorpsi Ion Tembaga (II) Menggunakan Silika Gel-GPTMS Termodifikasi Sulfonat - Setiowati, Fiqih Sekar; Oktavia, Budhi; Sanjaya, Hary; Putra, Ananda (Departemen Kimia FMIPA UNP, 2024)
Adsorption is a process of sorption onto a specific substance that occurs at the surface of a solid material due to intermolecular forces or the penetration of a substance into the solid material surface. Adsorption involves an adsorbent as the sorbent material and an adsorbate as the component being sorbed. Silica gel is a commonly employed adsorbent for the sorption of Cu2+ ions. It is utilized as an adsorbent due to the presence of silanol and siloxane groups, which serve as active sites that can be modified. The modification aims to enhance the adsorption capacity of silica gel for Cu2+ metal ions. In aquatic environments, Cu metal ions are highly toxic to living organisms, posing significant hazards. The modifying compound employed in this study is monosodium salt of 4 – amino – 5 – hydorxy – 2,7 – naphthalenedisulfonic acid. However, prior to the sulfonate compound modification, a linking compound, γ-glycidoxypropyltrimethoxysilane (GPTMS), is required. The purpose of this study was to determine the effect of variations in pH and contact time on the adsorption of Cu2+ metal ions on sulfonate modified silica gel – GPTMS. The modified silica gel was characterized using Fourier-transform infrared (FTIR). The adsorption of Cu2+ ions was characterized by specific surface area (SSA), and the optimal adsorption conditions were determined as pH 4 and contact time of 60 minutes.